(untitled) (Communication & Society, 2018)
This article reviews the professional profile of the showrunner in the audiovisual industry, from a historical and conceptual perspective: the background, the features that define it, and the TV media position. To do so, qualitative methodology has been used to conduct a thorough bibliographic review, and examine the emergence and development of the “showrunner” concept in television history, and the term used to describe it. We then analysed the “executive producer” and “creative producer” categories, both of which are associated with the objective of the study, to determine a generalized definition of the audiovisual showrunner. We have also examined the characteristics associated with this professional producer and writer position, the skill set required for the same, the roles and responsibilities to be managed during the production process, and the creative hallmark of authorship over the TV series. Finally, the results obtained suggest that this writer-producer position has existed since the onset of the television industry; however, the use of the term “showrunner” is more recent. Today, we see a revaluation of this profile in TV series production thanks to the generalized use of the concept “showrunner”, and due to several historical, cultural, and technological factors that contribute to this situation.